The depleted mineralization of the fungicide chlorothalonil derived from loss in soil microbial diversity. Issue 1 (December 2017) - Souza, Adijailton; Andrade, Pedro; Araújo Pereira, Arthur; Andreote, Fernando; Tornisielo, Valdemar; Regitano, Jussara
Abstract There are lack of studies regarding the effects of microbial diversity on specific soil functions, such as pesticides degradation. This study evaluated the role of bacterial community diversity and biochar on chlorothalonil (CTN) degradation, using 'dilution to extinction' approach, PCR-DGGE/16S rRNA gene technique, and radiorespirometry (14 C-CTN). Biochar and microbial community dilution affected structure of the microbial community. In spite of that, CTN mineralization was slow, but dissipation was very fast (D50  < 1.0 d) due to immediate chemical degradation and formation of non-extractable (bound) residues. However, any depletion on soil microbial diversity strongly affected CTN mineralization, suggesting that this function is related to less abundant but specific microbial groups (CTN degraders) or to soil microbial diversity. The extent of these effects will strongly depend on the compound nature (recalcitrance) and soil matrix/substrate (bioavailability). It can be corroborated by the fact that biochar affected CTN sorption, its bioavailability, and subsequently its mineralization rate in the NS. These data indicate a strong relationship between soil microbial diversity and pesticide degradation, which is an acting form to mitigate xenobiotics accumulation in the environment.